Bentuk Perlindungan Dan Pertanggungjawaban Terhadap Hak-Hak Anak Dalam Konflik Bersenjata - Ferrara, Dendy Anugrah; Wattimena, Josiana Agusthina Yvonne; Hanafi, Irma Halima (Faculty of Law Universitas Pattimura, 2024)
The armed conflict that occurred in Afghanistan in 2001 and the use of child soldiers in the Congo conflict in 1996 are types of conflicts related to human rights that require protection and accountability in accordance with International Law which regulates the Geneva Conventions 1949, Additional Protocols I and II 1977, Rome Statute 1998, and Optional Protocols. The problems studied include: First, how is the protection of children's rights in situations of armed conflict. How is the responsibility of the relevant parties to the protection of children's rights in armed conflict. The research method used is normative juridical by using case approach, conceptual approach, and statutory approach. The purpose of the research is to analyze and find out the form of protection of children's rights in situations of armed conflict, as well as the responsibility of the parties concerned for the protection of children's rights in armed conflict. The results of this study explain that the form of protection of children's rights in situations of armed conflict consists of preventive legal protection regulated in the 1949 Geneva Convention Additional Protocol I Article 51 Paragraphs 1 to 3, and repressive legal protection related to legal protection for children recruited as child soldiers based on the 1989 Convention on the Rights of the Child regulated in Article 38. The final mechanism for accountability to parties who recruit children to serve as soldiers can be tried at the International Criminal Court (ICC). Thus, there is a need to harmonize the provisions of armed conflict and the protection of children's rights in International Law. Each state must ensure effective law enforcement as a means of accountability for violations of International Law, including through thorough investigations and fair trials of perpetrators of violations involving the use of child soldiers.